1996
DOI: 10.2165/00019053-199609010-00006
|View full text |Cite
|
Sign up to set email alerts
|

Economic Evaluation of Vaccination Against Influenza in New Zealand

Abstract: The objective of this study was to evaluate the costs and benefits of influenza vaccination for the population aged 65 years and over, from the perspectives of individuals and health insurers, government and society. The annual incremental direct medical costs and benefits of influenza vaccination (compared with the nonvaccination, or 'do nothing', option) were evaluated using New Zealand healthcare resource usage and unit cost data [in 1992 New Zealand dollars ($NZ); $NZ1 = $US0.5458, June 1992] applied to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 8 publications
0
18
0
1
Order By: Relevance
“…Other studies have found vaccination to be cost saving [288,289]. In elderly persons, vaccination has also been cost-saving [275,[290][291][292]. Vaccination is probably also cost-saving relative to providing anti-viral treatment with neuraminidase inhibitors [293].…”
Section: Is Vaccination Cost-effective?mentioning
confidence: 99%
“…Other studies have found vaccination to be cost saving [288,289]. In elderly persons, vaccination has also been cost-saving [275,[290][291][292]. Vaccination is probably also cost-saving relative to providing anti-viral treatment with neuraminidase inhibitors [293].…”
Section: Is Vaccination Cost-effective?mentioning
confidence: 99%
“…A placebocontrolled trial 22 from the Netherlands confirmed that vaccination reduced clinical and serologic influenza illness among the elderly by 58%. Observational studies [39][40][41][42][43][44][45][46][47][48][49][50] from the United States, Canada, and the United Kingdom have demonstrated that vaccination is associated with lower rates of complications of influenza such as hospitalization for pneumonia and influenza and for pneumonia together with other respiratory conditions. 47,50 Several studies have also shown lower death rates from all causes 47,51 or from influenza.…”
Section: Commentmentioning
confidence: 99%
“…As there are no contraindications to vaccination other than Guillain-Barré Syndrome or anaphylaxis to eggs, there is no need for a physician visit in order to receive influenza vaccine. Studies in Canada [29], Europe [30,31], New Zealand [32] and Taiwan [33] have had similar findings.…”
Section: Who Should Be Vaccinated?mentioning
confidence: 56%